Contribuição ao conhecimento de alguns Ithomiidae brasileiros, predadores de Solanáceas (Lep., Rhopalocera) - Lordello, Luiz Gonzaga E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1950)
This paper is a small contribution to the knowledge of some species of brazilian Ithomiidae (Lep., Rhop.). The Author, during the year 1950, had an oportunity to study the development of the following species: Mechanitis lysimnia Fabr. Mechanitis polymnia casabranca Hsch. Dircenna dero Hübn. Methona themisto (Hübn.) The three first species live, in Piracicaba (State of São Paulo, Brasil), on Solanum variabile Mart., damaging its leaves, Mechanitis polymnia casàbranca being a serious enemy of this medicinal plant. The Author presents some notes on the biological cycle of M. lysimnia, which confirm D'Almeida's observations. Methona themisto is an old pest of Brunfelsia hopeana Benth. In Argentine, according to Hayward's observations, it occurs on Brunfelsia pauciflora Benth. The biology of this species previously has been studied by Figueiredo (1939). In Piracicaba it is not an enemy of B. hopeana on which it is reported to be so harmful elsewhere. The Author's observations were made in the Laboratory of Zoology of the Escola Superior de Agricultura "Luiz de Queiroz" in order to protect the larvae from the attack of their possible natural enemies. Notwithstanding, the Mechanitis polymnia casabranca caterpillars were attacked by an interesting Salticidae, identified by Hélio Camargo as Hasarius adan-soni (Audouin, 1827).